PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN, KEPERCAYAAN DAN RELIGIUSITAS TERHADAP MINAT BERWAKAF UANG MENGGUNAKAN APLIKASI WAKAF - Akbar, Taufik; Zaerofi, Afif (Manis: Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze the influence of perceived ease of use, trust, and religiosity on the behavioral intention to perform cash waqf through a waqf application in the Jabodetabek area (Jakarta, Bogor, Depok, Tangerang, and Bekasi). This study employs a quantitative approach with a survey method to collect data from internet users who have participated in waqf through waqf applications or websites. Statistical techniques are used for data analysis to test the proposed hypotheses, and the analytical tool applied is SEM-PLS. The results showed that the three variables had a significant influence on interest in using the cash waqf application. Perceived Ease of Use acts as a major factor in technology adoption, where the ease of use of the application increases user interest. In addition, a high level of religiosity encourages individuals to be more interested in waqf through digital applications. Trust in transparency, security, and management of funds according to sharia principles also plays an important role in increasing user interest. The implications of these findings indicate the importance of waqf application providers to improve ease of use, transparency, and features that support religious values to attract more users. The findings are expected to provide insights into the future development of digital-based waqf applications. Future research could expand the research variables and apply a qualitative approach to dig deeper into the user experience.